A Multilevel Analysis of Factors Associated with Teenage Pregnancy in Ethiopia - Kefale, Bereket (Int J Womens Health, 2020)
BACKGROUND: A significant number of girls in Ethiopia begin childbearing at an early age. Teenage pregnancy is the main contributor to maternal and child morbidity and mortality, and the vicious cycle of ill-health and poverty. However limited evidence exists about individual- and community-level factors affecting teenage pregnancy in Ethiopia. METHODS: This study used data from the 2016 Ethiopian Demographic and Health Survey (EDHS). A total of 3381 (weighted) teenagers aged 15–19 years were included in the study. A two-stage stratified cluster was used. Data were analyzed using Stata version 14. Multilevel mixed effect logistic regression was used to identify factors affecting teenage pregnancy. RESULTS: Being 17 (AOR=9.26, 95% CI=2.67–32.04), 18 (AOR=9.53, 95% CI=2.97–30.04) and 19 years old (AOR=20.01, 95% CI=5.94–67.39), uneducated (AOR=3.83, 95% CI=1.05–14.00), primary educated (AOR=3.34, 95% CI=1.01–11.08), being married (AOR=70.12, 95% CI=27.55–178.4), and communities with a higher proportion of poor (AOR=3.86, 95% CI=1.80–8.26) were predictors of teenage pregnancy. CONCLUSION: Age, educational status, and marital status from individual-level factors, and community wealth status from community-level factors were predictors of teenage pregnancy. The government should strive to improve female education, and fight against early marriage and sexual initiation.